MicroRNA‐1307‐3p contributes to breast cancer progression through PRM2 - José Roberto Estupiñan‐Jiménez; Valeria Villarreal‐García; Vianey Gonzalez‐Villasana; Pablo E. Vivas‐Mejia; Jose Manuel Vazquez‐Guillen; Patricio Adrián Zapata‐Morin; Marienid Flores‐Colón; Claudia Altamirano‐Torres; Ezequiel Viveros‐Valdez; Cristina Ivan; Mohammed H. Rashed; Recep Bayraktar; et al. (Thoracic Cancer)
Abstract Background Despite advances in screening and therapy, breast cancer (BC) remains the predominant cancer in women globally. Dysregulation of microRNAs (miRNAs) is pivotal in carcinogenesis across various cancers, including BC. Evidence indicates that miR‐1307‐3p is upregulated in BC tumors, yet its target genes are not fully elucidated. This study aimed to explore how miR‐1307‐3p regulates BC proliferation, migration, invasion, and angiogenesis and to identify potential target genes. Methods Basal miR‐1307‐3p levels were quantified in BC cell lines MDA‐MB‐231 and MCF‐7, as well as MCF‐10A using quantitative real‐time reverse transcription‐PCR (RT‐qPCR). The impact of miR‐1307‐3p inhibition on BC cell proliferation, migration, invasion, and angiogenesis was assessed. Nine miRNA‐target prediction databases identified potential miR‐1307‐3p targets. Target expression was validated using RT‐qPCR, Western blot, and dual‐luciferase reporter assays. MiR‐1307‐3p was overexpressed in MDA‐MB‐231 and MCF‐7 compared to MCF‐10A. Results Inhibiting miR‐1307‐3p significantly reduced BC cell proliferation, migration, invasion, and angiogenesis. Bioinformatics analysis identified 17 potential miR‐1307‐3p targets, with protamine 2 (PRM2) overexpression confirmed via Western blot and dual‐luciferase assays. Conclusion MiR‐1307‐3p overexpression in BC promotes proliferation, migration, invasion, and angiogenesis. PRM2 emerges as a novel miR‐1307‐3p target in BC.